Prevalence of Thalassemia in Children in Africa: A Systematic Review and Meta-Analysis - Habibatou, Ide Amadou; Ounoussa, Tapha; Zaratou, Ali; Nadakou, N’Kpingou Theodore; Oumou, Hamidou; Aminata, Mamane Daouda; Abdoulaye, Ousmane; Boutchi, Mounkaila (European Scientific Journal, ESJ, 2025)
Thalassemia is a blood disorder caused by numerous inherited mutations in the globin gene. This meta-analysis aimed to provide an update on the prevalence of thalassemia in Africa between 2007 and 2025. A systematic literature search was conducted across the PubMed, AJOL, and Google Scholar databases to identify studies published between 2007 and 2025, using specific inclusion and exclusion criteria. Quality assessment was performed using the Mixed Methods Appraisal Tool (MMAT) for prevalence studies. The heterogeneity of the included studies was assessed using the I2 and Q statistics. Funnel plots and Egger tests were performed to determine publication bias in this meta-analysis. The pooled 95% confidence interval (95% CI) prevalence of thalassemia across studies was determined using a generic random-effects inverse-variance method. Eleven studies involving 26025 subjects were included, and the prevalence rates were pooled using random-effects models due to high observed heterogeneity (I2 > 75%, p-value < 0.05). The overall prevalence of thalassemia was 13.4% (95% CI 8.5-19.1%, I2 = 99.1%). Subgroup analyses showed that the pooled prevalence of thalassemia was 14% (95% CI, 0-33%; I² = 98.5%) in neonates, 22% (95% CI, 11-33%; I² = 98.8%) in patients ≤ 5 years of age and 6% (95% CI, 3-9%; I² = 82.6%) in patients over 5 years of age. The prevalence of alpha-thalassemia carriers was 18% (95% CI, 7-28%; I² = 99.2%) and beta-thalassemia 9% (95% CI, 6-12%; I² = 98.6%). This meta-analysis suggests a high prevalence of thalassemia in certain African countries. These data help design thalassemia screening programs and improve disease management.